2013
DOI: 10.1038/pr.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

Packed red cell transfusions alter mesenteric arterial reactivity and nitric oxide pathway in preterm lambs

Abstract: BACKGROUND Cases of necrotizing enterocolitis occurring within 48 h of packed red blood cell (PRBC) transfusions are increasingly being described in observational studies. Transfusion-associated gut injury is speculated to result from an abnormal mesenteric vascular response to transfusion. However, the mechanism of disruption of the balance between mesenteric vasoconstriction and relaxation following transfusion is not known. METHODS Preterm lambs (n = 16, 134 d gestation; term: 145–147 d) were delivered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The effect of blood transfusion on splanchnic vasculature is reliant on the balance between mesenteric vasoconstriction and relaxation induced by intestinal endothelial production of nitric oxide. A recent study has shown blood transfusion in enterally fed preterm lambs (n = 16) promotes mesenteric vasoconstriction and impairs vasorelaxation by reducing mesenteric arterial endothelial nitric oxide synthase …”
mentioning
confidence: 99%
“…The effect of blood transfusion on splanchnic vasculature is reliant on the balance between mesenteric vasoconstriction and relaxation induced by intestinal endothelial production of nitric oxide. A recent study has shown blood transfusion in enterally fed preterm lambs (n = 16) promotes mesenteric vasoconstriction and impairs vasorelaxation by reducing mesenteric arterial endothelial nitric oxide synthase …”
mentioning
confidence: 99%
“…The number of subjects in each group is small. However, we performed a power analysis of our study using previous published data demonstrating that vasoconstriction to NE is normally distributed with a standard deviation of 401 g/g force in 134-d gestation lambs (6). To detect a difference of 800 g/g force of contraction between the groups, we needed at least four lambs in each group.…”
Section: Discussionmentioning
confidence: 99%
“…A temporal association between packed red blood cell transfusion and NEC has been reported (4,5). Packed red blood cell transfusion has also been shown to increase mesenteric arterial (MA) contractility in preterm fed lambs (6). NO is thought to play a key role as a molecular signaling “hub” in the generation of gut barrier failure in NEC (7) as well as in the pathogenesis of transfusion-associated gut injury (8).…”
mentioning
confidence: 99%
“…30 An alternative explanation is an immunologic influence working through mesenteric arterial reactivity and nitric oxide pathways as investigated in premature lambs. 173 So far, however, evidence has been equivocal, 174,175 and a recent meta-analysis, found that the quality of the studies on transfusion induced NEC was generally low.…”
Section: Pathophysiologymentioning
confidence: 99%